Susceptibility based multiparametric quantification of liver disease: non-invasive evaluation of steatosis and iron overload - Uhrig, Monika; Müller, Johannes; Longerich, Thomas; Straub, Beate Katharina; Buschle, Lukas R.; Schlemmer, Heinz-Peter; Mueller, Sebastian; Ziener, Christian H. (Magnetic resonance imaging, 2019)
Purpose - To evaluate if single-voxel MR spectroscopy (MRS) of iron and fat correlates with biopsy results of hepatic steatosis and iron overload, and to compare MR-measurements with room-temperature susceptometer (RTS), ultrasound, controlled attenuation parameter (CAP) and serum ferritin. - Material and methods - In this prospective study, a set of 42 patients out of 47 screened patients with several chronic liver diseases underwent MRI-examination at 1.5T including R2-measurements by single-voxel high-speed T2-corrected multiecho spectroscopy, additional liver biopsy, abdominal ultrasound, CAP, and RTS. Routine blood and serum parameters were determined, including ferritin. Atomic absorption spectroscopy (AAS) and histologically confirmed extent of hepatic steatosis from liver biopsy were used as reference standard. For correlation of R2, RTS, CAP, ferritin, and ultrasound with results of AAS and histologically determined fat fraction of liver biopsy specimen, Spearman's and Pearson's correlation as well as receiver operating characteristics curve (ROC) analysis with cut-off values determined by maximizing Youden index was used. - Results - MRS iron assessment correlated best with AAS, with a Pearson correlation coefficient of 0.715 (p<0.001), followed by RTS 0.520 (p<0.001), and serum ferritin 0.213 (p=0.088, not significant). MRS fat quantification correlated best with the histological confirmed extent of steatosis hepatis with a Spearman correlation coefficient of 0.836 (p<0.001), followed by CAP 0.604 (p<0.001) and sonographically diagnosed steatosis 0.358 (p=0.013). - Conclusion - MRS by T2-corrected multiecho single-voxel spectroscopy correlated best with histological results of hepatic fat and iron content compared to RTS, CAP, abdominal ultrasound, and ferritin. Non-invasive methods to assess hepatic fat and iron are of clinical interest for follow-up examinations of patients with chronic liver diseases, where repeated biopsy is not indicated.